Smoking identified as preferred mode of opioid safe supply use; investigating correlates of smoking preference through a 2021 cross-sectional study in British Columbia - Ariba Kamal; Max Ferguson; Jessica C Xavier; Lisa Liu; Brittany Graham; Kurt Lock; Jane A. Buxton (Substance Abuse Treatment, Prevention, and Policy, 2023)
Abstract Background The increasing number of illicit drug toxicity deaths in British Columbia (BC) has led to calls for a regulated (pharmaceutical grade) supply of substances (“safe supply”). In order to inform safe supply recommendations, we aimed to identify why people currently smoke opioids and assess the preferred mode of consumption if people who use opioids were provided with opioid safe supply. Methods The BC Harm Reduction Client Survey (HRCS) is an annual survey that gathers information about people who use drugs' (PWUD) substance use characteristic with the goal of contributing to evidence-based policy. This study utilized data from the 2021 HRCS. The outcome variable was “prefer smoking opioid safe supply” (‘yes/no’). Explanatory variables included participants’ demographics, drug use, and overdose characteristics. Bivariate and hierarchical multivariable logistic regressions were conducted to identify factors associated with the outcome. Results Of 282 total participants who indicated a preference for a mode of consumption for opioid safe supply, 62.4% preferred a smokable option and 19.9% preferred to inject if provided with opioid safe supply. Variables significantly associated with the outcome (preferred smoking) included: being 19-29 years old (AOR=5.95, CI =1.93 – 18.31) compared to >50 years old, having witnessed an overdose in the last 6 months (AOR=2.26, CI=1.20 – 4.28), having smoked opioids in the last 3 days (AOR=6.35, CI=2.98 – 13.53) and having a preference to smoke stimulants safe supply (AOR=5.04, CI=2.53 – 10.07). Conclusion We found that over half of participants prefer smokable options when accessing opioid safe supply. Currently in BC, there are limited smokable opioid safe supply options as alternatives to the toxic street supply. To reduce overdose deaths, safe supply options should be expanded to accommodate PWUD that prefer smoking opioids.